Effective Approach for Increasing the Heteroatom Doping Levels of Porous Carbons for Superior CO2 Capture and Separation Performance - Abdelmoaty, Yomna H (2017)
Development of efficient sorbents for carbon dioxide (CO2) capture from flue gas or its removal from natural gas and landfill gas is very important for environmental protection. A new series of heteroatom-doped porous carbon was synthesized directly from pyrazole/KOH by thermolysis. The resulting pyrazole-derived carbons (PYDCs) are highly doped with nitrogen (14.9–15.5 wt %) as a result of the high nitrogen-to-carbon ratio in pyrazole (43 wt %) and also have a high oxygen content (16.4–18.4 wt %). PYDCs have a high surface area (SABET = 1266–2013 m2 g–1), high CO2 Qst (33.2–37.1 kJ mol–1), and a combination of mesoporous and microporous pores. PYDCs exhibit significantly high CO2 uptakes that reach 2.15 and 6.06 mmol g–1 at 0.15 and 1 bar, respectively, at 298 K. At 273 K, the CO2 uptake improves to 3.7 and 8.59 mmol g–1 at 0.15 and 1 bar, respectively. The reported porous carbons also show significantly high adsorption selectivity for CO2/N2 (128) and CO2/CH4 (13.4) according to ideal adsorbed solution theory calculations at 298 K. Gas breakthrough studies of CO2/N2 (10:90) at 298 K showed that PYDCs display excellent separation properties. The ability to tailor the physical properties of PYDCs as well as their chemical composition provides an effective strategy for designing efficient CO2 sorbents.